The Effect Of Compensation And Working Environment On Turnover Intention In PT.Putra Dolok Mandiri - Rini Laraswani; Risa Kartika Lubis (Institute of Computer Science (IOCS), 2020)
This study aims to determine: 1) The effect of compensation on Turnover Intention at PT. Putra Dolok Mandiri, 2) The Effect of Work Environment on Turnover Intention at PT. Putra Dolok Mandiri, 3) The Effect of Compensation and Work Environment on Turnover Intention at PT. Putra Dolok Mandiri. This study uses a quantitative approach. The sample in this study were employees of PT. Putra Dolok Mandiri, amounting to 37 people. Data collection used questionnaires and interviews, while data analysis used multiple linear regression analysis. Based on the results of this study, it is known that there is a significant effect of compensation and work environment on turnover intention at PT. Putra Dolok Mandiri